2001
DOI: 10.1152/ajpcell.2001.281.5.c1635
|View full text |Cite
|
Sign up to set email alerts
|

Flow-induced calcium oscillations in rat osteoblasts are age, loading frequency, and shear stress dependent

Abstract: Bone adaptation to mechanical loading is dependent on age and the frequency and magnitude of loading. It is believed that load-induced fluid flow in the porous spaces of bone is an important signal that influences bone cell metabolism and bone adaptation. We used fluid flow-induced shear stress as a mechanical stimulus to study intracellular calcium (Ca) signaling in rat osteoblastic cells (ROB) isolated from young, mature, and old animals. Fluid flow produced higher magnitude and more abundant [Ca(2+)](i) osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
79
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 49 publications
8
79
0
Order By: Relevance
“…During oscillatory flow, we found that the cells deformed primarily like elastic bodies, in that the phase lags were small, and the normalized peak displacements were only weakly frequency-dependent. Previous experiments have demonstrated that osteoblasts exhibit a decrease in the number of cells exhibiting a flow-induced calcium response with increasing frequency of oscillatory fluid flow from 0.2-2.0Hz (Donahue et al 2001;Jacobs et al 1998). This frequency dependence has been attributed to cellular viscoelasticity, in that the cells may be deforming more at lower frequencies/loading rates, allowing the molecular mechanisms which "sense" cellular deformation (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During oscillatory flow, we found that the cells deformed primarily like elastic bodies, in that the phase lags were small, and the normalized peak displacements were only weakly frequency-dependent. Previous experiments have demonstrated that osteoblasts exhibit a decrease in the number of cells exhibiting a flow-induced calcium response with increasing frequency of oscillatory fluid flow from 0.2-2.0Hz (Donahue et al 2001;Jacobs et al 1998). This frequency dependence has been attributed to cellular viscoelasticity, in that the cells may be deforming more at lower frequencies/loading rates, allowing the molecular mechanisms which "sense" cellular deformation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Exposing bone cells to static versus dynamic flow profiles has also been shown to induce different biochemical and morphological responses (Malone et al 2007;Mullender et al 2006;Ponik et al 2006). This dependence on flow profile has been postulated to be due to viscoelastic behavior (Donahue et al 2001), since the cells may be deforming more at lower loading rates. However, assessing the extent to which this is occurring based on what is currently understood about cellular viscoelasticity (Alcaraz et al 2003;Balland et al 2006;Fabry et al 2003;Kole et al 2004;Puig-de-Morales et al 2001;Shroff et al 1995;Wilhelm et al 2003;Yamada et al 2000) is difficult for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic fluid flow is one of the mechanical stimuli that osteocytes experience in vivo with habitual loading (24,25,54). Previous studies have established that this loading-induced dynamic fluid flow is a potent physical signal in the regulation of bone cell metabolism (7,16,37,57), yet it is unclear what role it might play in osteocyte mediated regulation of bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] These results have been found in osteoblastic cell lines, and in primary bone cells from several species including humans. 8,[12][13][14][15][16][17][18][19] Specifically, the production of nitric oxide (NO) and prostaglandins (PG) is stimulated in bone cells in response to fluid flow. 8,[20][21][22][23] Osteocytes are more responsive than osteoblasts, whereas periostial fibroblasts show almost no response.…”
Section: Introductionmentioning
confidence: 99%